Recent Advances in the Pathogenesis of Steroid-induced Osteonecrosis of the Femoral Head - Chen, Qi; Zhang, Kun; Hao, Yangquan (Journal of Contemporary Medical Practice, 2025)
Steroid-induced osteonecrosis of the femoral head is an orthopedic disease caused by prolonged or excessive use of steroids, leading to bone necrosis and joint dysfunction in the femoral head. It has the highest incidence among non-traumatic femoral head osteonecrosis and is a major challenge in clinical orthopedic practice. In recent years, significant progress has been made in understanding the pathogenesis of steroid-induced osteonecrosis of the femoral head, with deeper studies into its etiology. This article aims to summarize the pathogenesis of steroid-induced osteonecrosis of the femoral head, with the goal of providing references for clinical treatment and basic research.